Poly delta-thiovalerolactone and preparation and depolymerization method thereof
By using a main catalyst and an alkyl mercaptan initiator in an organic solvent, the molecular weight and mechanical properties of polydelta-valerolone were successfully improved, and the problems of low molecular weight and poor mechanical properties of the material in the prior art were solved.
Patent Information
- Application Number
- CN202510149513.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-02-11
AI Technical Summary
The existing polyδ-valerolide has low molecular weight and poor mechanical properties, making it difficult to apply in industry.
Polydelta-thiovalerolide with high molecular weight was prepared by performing polymerization reactions of 80 to 120°C using a main catalyst and an alkylthiol initiator in an organic solvent.
The number average molecular weight of polyδ-thiovalerolone is significantly improved, and its mechanical properties are improved, making it a strong and tough semi-crystalline material with mechanical properties comparable to low-density polyethylene.
Smart Images

Figure CN119899383A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer synthesis and relates to polydelta-thiovalerolactone and a preparation and depolymerization method thereof. Background Art
[0002] Plastics are a class of ubiquitous synthetic polymer materials used in almost all commercial and industrial fields. Since the 1950s, the growth rate of plastic production has exceeded that of any other class of man-made materials, and it is expected that by 2050, the future growth of petrochemical products, including plastics, will account for half of the global oil demand. As a new type of material, chemically recyclable polymers can be depolymerized into polymer precursors after use, avoiding polymer pollution and providing raw materials for polymer production, effectively improving the "white pollution" problem of plastics. δ-Valerolactone is a commercial reagent that forms chemically recyclable polymers through ring-opening polymerization, and the formed polyester is also biodegradable. Therefore, polyδ-valerolactone is a very valuable green polymer material. However, the operating temperature of this type of polymer is lower than 56°C, and the heat resistance is poor (the melting point of polyδ-valerolactone is 56°C). Therefore, improving the melting point of this type of polymer is a difficult point in research in this field.
[0003] By changing the CO single bond in δ-valerolactone to a CS single bond, the melting point of the formed polyδ-thiovalerolactone is increased to 123°C, which significantly improves the heat resistance of the polymer. At the same time, the polymer main chain has a thioester functional group, which ensures the degradability of the polymer. However, due to the poor orbital overlap between the 3P orbital of the sulfur atom and the 2P orbital of the oxygen atom, it is relatively difficult for the lone pair of electrons of the single-bonded sulfur atom in the thioester bond to delocalize to the carbonyl carbon connected to it. Therefore, the thioester is more electrophilic and more susceptible to nucleophilic attack. The stability of thiolactone is poor. Thioester exchange reactions are common in the synthesis process. The synthesis of high molecular weight polyδ-thiovalerolactone is a very challenging problem. At present, the preparation of polyδ-thiovalerolactone can be obtained by three methods: 1) ring-opening polymerization of δ-thiocarbonyl valerolactone; 2) ring-opening polymerization of δ-thiovalerolactone; 3) self-polymerization of 4-pentenethioic acid, as follows:
[0004] Ring-opening polymerization of δ-thiocarboxyvalerolactone: δ-thiocarboxyvalerolactone has a renewable green source and low cost. It can be obtained with high yield by direct thiolation using commercial δ-valerolactone as raw material, and can be synthesized on a large scale industrially. However, δ-thiocarboxyvalerolactone has high thermodynamic stability and is difficult to polymerize. Currently, there is only one report on the ring-opening polymerization of δ-thiocarboxyvalerolactone (ACS Macro Lett. 2024, 13, 1411). The polyδ-thiocarboxyvalerolactone obtained in this literature has a low molecular weight (number average molecular weight M n :1.3~14.3kg / mol), poor mechanical properties and no application value.
[0005] δ-thiovalerolactone ring-opening polymerization: Compared with δ-thiocarbovalerolactone, δ-thiovalerolactone is difficult to synthesize, the raw material price is high, and the yield is low. The ring-opening polymerization of δ-thiovalerolactone is also difficult. Currently, there are only two literature reports on the preparation of polyδ-thiovalerolactone by ring-opening polymerization of δ-thiovalerolactone. The polyδ-thiovalerolactone obtained by anionic polymerization by Overberger's group (J.Am.Chem.Soc.1968,90,3533) has a low molecular weight (number average molecular weight M n ~1.0kg / mol), the molecular weight of polyδ-thiovalerolactone obtained by Gutekunst using organic base and alkyl mercaptan is also very low (number average molecular weight M n ~14.3kg / mol)(ACSMacro Lett.2022,11,895), poor mechanical properties and no application value.
[0006] 4-pentenethioic acid self-polymerization: The self-polymerization process of 4-pentenethioic acid is uncontrollable, the monomer synthesis is very difficult, and the obtained polyδ-thiovalerolactone has a low molecular weight (number average molecular weight M n ~1.0kg / mol).
[0007] Therefore, the number average molecular weight of the polyδ-thiovalerolactone reported so far is lower than 14.3 kg / mol, the mechanical properties are poor, and there is no application value. The development of high molecular weight polyδ-thiovalerolactone with excellent mechanical properties is still a technical gap. Summary of the invention
[0008] The technical problem to be solved by the present invention is to overcome the defects of low molecular weight and poor mechanical properties of existing polyδ-thiovalerolactone (PTVL), and provide polyδ-thiovalerolactone and a preparation method thereof. The number average molecular weight of the polyδ-thiovalerolactone prepared by the preparation method of the present invention is significantly improved, and the polyδ-thiovalerolactone has good mechanical properties.
[0009] The technical solution of the present invention:
[0010] A polyδ-thiovalerolactone, a polymer represented by formula (I), has a structure as shown below:
[0011]
[0012] Here, n is greater than or equal to 138.
[0013] According to the common knowledge of polymer chemistry, in the compound represented by formula (I), each structure in “()” represents a structural unit; the n is the degree of polymerization, which is also the number average degree of polymerization or the average degree of polymerization.
[0014] Said n is preferably 138-10000, more preferably 250-5000, such as 250, 600, 1000, 2000 or 5000.
[0015] The number average molecular weight of the compound represented by formula (I) is preferably greater than or equal to 16.0 kg / mol, more preferably 29.0-580 kg / mol, such as 29.0 kg / mol, 99.9 kg / mol, 101 kg / mol, 195 kg / mol, 249 kg / mol or 580 kg / mol.
[0016] The molecular weight distribution of the compound represented by formula (I) is 1.0-3.0, preferably 1.0-2.5, such as 1.0, 1.1, 1.2, 1.5, 2.0, 2.5 or 3.0.
[0017] The present invention also provides a method for preparing polyδ-thiovalerolactone shown in formula (I), comprising the following steps: in an organic solvent, in the presence of a main catalyst and an alkylthiol initiator, polymerizing the compound shown in formula (II) at 80-120°C.
[0018]
[0019] The main catalyst is one or a mixture of two or more of amidine organic bases, guanidine organic bases, N-heterocyclic carbene organic bases, and N-heterocyclic olefin organic bases, preferably amidine organic bases.
[0020] In the method for preparing the compound as shown in formula (I), the organic solvent may be a conventional organic solvent in the art, preferably a hydrocarbon solvent, a halogenated aromatic solvent, or a mixture of two or more thereof, more preferably an aromatic solvent and / or a halogenated aromatic solvent, more preferably toluene and / or o-dichlorobenzene. When the organic solvent is an aromatic solvent, the aromatic solvent is a mixture of one or more thereof selected from toluene, benzene, and xylene, preferably toluene; when the organic solvent is a halogenated aromatic solvent, the halogenated aromatic solvent is a mixture of one or more thereof selected from o-dichlorobenzene, o-difluorobenzene, o-dibromobenzene, chlorobenzene, fluorobenzene, bromobenzene, and iso-trichlorobenzene, preferably o-dichlorobenzene.
[0021] In the method for preparing the compound of formula (I), the amidine organic base is a conventional amidine organic base in the art, preferably 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU, formula III), the structure of which is shown below:
[0022]
[0023] In the method for preparing the compound of formula (I), the guanidine organic base is a conventional guanidine organic base in the art, preferably 1,5,7-triazidebicyclo(4.4.0)dec-5-ene (TBD, formula IV) and / or 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (MTBD, formula V), the structure of which is shown below:
[0024]
[0025] In the preparation method of the compound shown in formula (I), the carbene organic base is a compound shown in formula (VI), and its structure is shown below:
[0026]
[0027] Among them, R 1 and R 2 R is independently hydrogen, a hydrocarbon group of 1 to 20 carbon atoms or an aromatic group of 6 to 20 carbon atoms, which may be the same or different; 3 and R 4 They are independently a hydrocarbon group of 1 to 20 carbon atoms or an aryl group of 6 to 20 carbon atoms, which may be the same or different.
[0028] In the preparation method of the compound shown in formula (I), the N-heterocyclic carbene organic base is a compound shown in formula (VII), and its structure is shown below:
[0029]
[0030] Among them, R 6 and R 7 R is independently hydrogen, a hydrocarbon group of 1 to 20 carbon atoms or an aromatic group of 6 to 20 carbon atoms, which may be the same or different; 5 and R 8 R is independently a hydrocarbon group of 1 to 20 carbon atoms or an aryl group of 6 to 30 carbon atoms; 9 and R 10 are independently hydrogen, methyl or ethyl;
[0031] In the method for preparing the compound as shown in formula (I), the alkylthiol initiator is R 11 SH, HSR 12 SH, R 13 (SH)3 and R 14 (SH) 4 or more, R 11 , R 12 , R 13 and R 14 It is a hydrocarbon group of 1 to 20 carbon atoms.
[0032] In the method for preparing the compound of formula (I), the molar ratio of the compound of formula (II) to the main catalyst is 100:1-10000:1;
[0033] In the method for preparing the compound represented by formula (I), the molar ratio of the initiator to the main catalyst is 1:1 to 100:1.
[0034] In the method for preparing the compound represented by formula (I), the polymerization reaction time is 5-1440 minutes.
[0035] The present invention realizes the preparation of a high molecular weight polymer represented by formula (I) by using a compound represented by formula (II) through the following strategy: using an alkylthiol reagent with strong nucleophilicity as an initiator. The nucleophilicity of the reagent is significantly better than that of aromatic thiols, aromatic alcohols and thioacetic acid reagents reported in the literature. The strong nucleophilic reagent makes the polymerization reaction easier to proceed, avoids ester exchange between polymer chains, and is conducive to the improvement of the degree of polymerization of the polymer.
[0036] Without violating the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0037] The reagents and raw materials used in the present invention are commercially available.
[0038] The polyδ-thiovalerolactone provided by the present invention is a strong and tough semi-crystalline material with a melting temperature of 123°C, which is similar to commercial low-density polyethylene, and has equivalent mechanical properties to commercial low-density polyethylene. It can also be rapidly and controllably degraded into δ-thiovalerolactone under specific conditions. Therefore, the δ-thiovalerolactone provided by the present invention is a potential green substitute for low-density polyethylene.
[0039] The present invention also provides a depolymerization method of the aforementioned δ-thiovalerolactone, comprising: mixing δ-thiovalerolactone with an acidic catalyst, and distilling at 100 to 350° C. (e.g., 100° C., 150° C., 200° C., 250° C., 300° C., 350° C.) under normal pressure or reduced pressure to obtain a lactone monomer having a structure shown in formula (VIII):
[0040]
[0041] Furthermore, the acidic catalyst includes one or a combination of two or more of zinc chloride, ferrous chloride, ferric chloride, zinc acetate, stannous octoate and phosphomolybdic acid.
[0042] Further, the acidic catalyst accounts for 0.1-50% (e.g., 0.1%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%) of the weight of delta-thiovalerolactone.
[0043] Beneficial effects of the invention: The preparation method of the invention effectively reduces the side reactions in the polymerization process, so that the monomer can be converted into polyδ-thiovalerolactone at a high conversion rate. Compared with the method reported in the literature, a high molecular weight polyδ-thiovalerolactone that cannot be synthesized in the literature is obtained, and the increase in molecular weight can significantly improve the mechanical properties of the polymer. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is the NMR of the polymerized monomer formula (II) δ-thiocarbonylvalerolactone.
[0045] Figure 2 This is a nuclear magnetic resonance comparison diagram of the polyδ-thiovalerolactone of Example 4 of the present invention and the formula (VIII) and δ-thiovalerolactone recovered by chemical recycling degradation.
[0046] Figure 3 It is a mechanical property test diagram of the polyδ-thiovalerolactone of Comparative Example 1 and Example 7 of the present invention.
[0047] Figure 4 This is the rheological test result of polyδ-thiovalerolactone. The entanglement molecular weight of the polymer is 16kg / mol. The polymer molecular weight exceeds 16kg / mol to show good mechanical properties. DETAILED DESCRIPTION
[0048] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.
[0049] Example 1
[0050] The compound represented by formula (II) of the present invention is a homemade product, and its initial raw material is commercial δ-valerolactone, which is prepared by a one-step reaction. The preparation method is not particularly limited, and is preferably prepared according to the method described in the following document (Bioorg.Chem.2021,108,104650-104656.):
[0051] Add 22.2g of phosphorus pentasulfide and 54.2g of hexamethyldisiloxane to a 500mL three-necked bottle, add 200mL of acetonitrile and stir, then add 20.0g of δ-valerolactone, reflux and stir for 4h. After the reaction is completed, after the reaction temperature drops to room temperature, add 200mL of saturated potassium carbonate solution and stir for 30min, separate the liquids, extract the aqueous phase with acetonitrile three times, and combine the organic phases. Dry with anhydrous sodium sulfate, filter, spin dry, and collect the product by column chromatography with petroleum ether / ether gradient elution (30:1~1:1). Then add calcium hydride to the monomer and dry it for 3 days, then distill it under reduced pressure at 100mTorr and 75℃ and store it in a glove box for use.
[0052] The δ-thiovalerolactone monomer obtained by the present invention is a light yellow liquid. The mass of the δ-thiocarbonylvalerolactone monomer obtained is 20.9 g, and the calculated yield is 90%.
[0053] The present invention characterizes the obtained δ-thiocarbonyl valerolactone monomer by nuclear magnetic resonance (NMR). 1 H NMR spectrum Figure 1 As shown, it is consistent with the literature report, which proves that the δ-thiocarbonyl valerolactone monomer prepared by the present invention has the structure of formula (II).
[0054]
[0055] Example 2
[0056] At 80°C, in a pre-dried 10mL serum bottle, first weigh 2.0g (8.61mmol) of the monomer δ-thiocarbonyl valerolactone and prepare a 5 mol / L N,N-diethylformamide solution. Also weigh 2.17mg (0.0344mmol) of ethanethiol and 5.24mg (0.0344mmol) of catalyst DBU and add them to the above monomer δ-thiocarbonyl valerolactone N,N-diethylformamide solution. After 3 hours, add 5mL of trifluoroacetic acid / CDCl3 (10mg / mL) to immediately quench the polymerization reaction, and then use 1 H NMR was used to analyze the monomer conversion. The quenched mixture was then precipitated into cold methanol, filtered, washed three times with cold methanol to remove any unreacted monomer, and dried overnight in a vacuum oven at room temperature to a constant weight. 1.52 g of a light yellow solid was obtained. The average molecular weight of the polymer was 16.5 kg / mol and the molecular weight distribution was 2.03 as determined by gel chromatography. The melting point of the polymer was 123 °C as shown by DSC testing.
[0057] Example 3
[0058] At 100°C, in a pre-dried 10mL serum bottle, first weigh 1.0g (8.61mmol) of the monomer δ-thiocarbonylvalerolactone, and weigh 3.49mg (0.0172mmol) of the initiator n-dodecyl mercaptan and 2.62mg (0.0172mmol) of the catalyst DBU and dissolve them in 0.07mL of toluene. Mix well and add to the monomer δ-thiovalerolactone. After a while, add 5mL of benzoic acid / CDCl3 (10mg / mL) to immediately quench the polymerization reaction, and then use 1H-NMR was used to analyze the conversion of the monomers. The quenched mixture was then precipitated into cold methanol, filtered, washed three times with cold methanol to remove any unreacted monomers, and dried overnight in a vacuum oven at room temperature to a constant weight. 0.96 g of a light yellow solid was obtained. The average molecular weight of the polymer was 17.1 kg / mol and the molecular weight distribution was 1.71 as determined by gel chromatography. The melting point of the polymer was 123°C as shown by DSC testing.
[0059] Example 4
[0060] At 100°C, in a pre-dried 10mL serum bottle, first weigh 1g (8.61mmol) of the monomer δ-thiocarbonylvalerolactone, and weigh 2.71mg (0.00861mmol) of the initiator n-eicosethiol and 1.31mg (0.00861mmol) of the catalyst DBU and dissolve them in 0.07mL of toluene. Mix well and add to the monomer δ-thiovalerolactone. After a while, add 5mL of benzoic acid / CDCl3 (10mg / mL) to immediately quench the polymerization reaction, and then use 1 H-NMR was used to analyze the conversion of the monomers. The quenched mixture was then precipitated into cold methanol, filtered, washed three times with cold methanol to remove any unreacted monomers, and dried overnight in a vacuum oven at room temperature to a constant weight. 0.80 g of a pale yellow solid was obtained. The average molecular weight of the polymer was 19.5 kg / mol and the molecular weight distribution was 1.65 as determined by gel chromatography. The melting point of the polymer was 123°C as shown by DSC testing.
[0061] Example 5
[0062] At 100°C, in a pre-dried 10mL serum bottle, first weigh 2g (17.2mmol) of the monomer thiocarbonyl valerolactone, and weigh 0.27mg (0.0043mmol) of the initiator n-dodecyl mercaptan and 3.27mg (0.043mmol) of the catalyst DBU and dissolve them in 0.07mL of toluene. Mix well and add to the monomer δ-thiovalerolactone. After a while, add 5mL of benzoic acid / CDCl3 (10mg / mL) to immediately quench the polymerization reaction, and then use 1 H NMR was used to analyze the monomer conversion. The quenched mixture was then precipitated into cold methanol, filtered, washed three times with cold methanol to remove any unreacted monomer, and dried overnight in a vacuum oven at room temperature to a constant weight. 1.30 g of a light yellow solid was obtained. The average molecular weight of the polymer was determined by gel chromatography to be 92.1 kg / mol, the molecular weight distribution was 2.35, and the DSC test showed that the melting point of the polymer was 123°C.
[0063] Example 6
[0064] At 100°C, in a pre-dried 10 mL serum bottle, first weigh 1 g (8.61 mmol) of the monomer δ-thiocarbonyl valerolactone, and weigh 0.27 mg (0.0043 mmol) of the initiator n-dodecyl mercaptan and 3.27 mg (0.043 mmol) of the catalyst DBU and dissolve them in 0.07 mL of toluene. Mix well and add to the monomer δ-thiovalerolactone. After a while, add 5 mL of benzoic acid / CDCl3 (10 mg / mL) to immediately quench the polymerization reaction, and then use 1 H NMR was used to analyze the monomer conversion. The quenched mixture was then precipitated into cold methanol, filtered, washed three times with cold methanol to remove any unreacted monomer, and dried overnight in a vacuum oven at room temperature to a constant weight. 0.58 g of a light yellow solid was obtained. The average molecular weight of the polymer was 54.4 kg / mol and the molecular weight distribution was 2.35 as determined by gel chromatography. The melting point of the polymer was 123°C as shown by DSC testing.
[0065] Example 7
[0066] At 100°C, in a pre-dried 10mL serum bottle, first weigh 2.0g (17.2mmol) of the monomer δ-thiocarbonylvalerolactone, and weigh 3.48mg (0.0172mmol) of the initiator n-dodecyl mercaptan and 2.62mg (0.0172mmol) of the catalyst DBU and dissolve them in 0.07mL of toluene. Mix well and add to the monomer δ-thiovalerolactone. After a while, add 5mL of benzoic acid / CDCl3 (10mg / mL) to immediately quench the polymerization reaction, and then use 1 H NMR was used to analyze the monomer conversion. The quenched mixture was then precipitated into cold methanol, filtered, washed three times with cold methanol to remove any unreacted monomer, and dried overnight in a vacuum oven at room temperature to a constant weight. 1.60 g of a light yellow solid was obtained. The average molecular weight of the polymer was 31.4 kg / mol and the molecular weight distribution was 1.51 as determined by gel chromatography. The melting point of the polymer was 123 °C as shown by DSC testing.
[0067] Figure 3 The figure shows the mechanical properties test of the polymer formed in Example 7 of the present invention.
[0068] Example 8
[0069] 1.0 g of polyδ-thiovalerolactone obtained in Example 7 and 10 mg of phosphomolybdic acid were added to a round-bottom flask, and the vacuum degree was 0.07 torr and the temperature was 160° C. to obtain 0.97 g of δ-thiovalerolactone. The purity was greater than 99% as determined by nuclear magnetic resonance. Figure 4The NMR comparison diagram of Example 7 of the present invention, δ-thiovalerolactone recovered by chemical recycling degradation and the synthesized δ-thiovalerolactone monomer is shown.
[0070] Comparative Example 1
[0071] This comparative example is the polyδ-thiovalerolactone with the highest molecular weight reported, literature: Stellmach K.A.; Paul MKK; Xu M.; Su YL; Fu L.; Toland AR; Tran H.; Chen L.; Ramprasad R.; Gutekunst WRACS Macro Lett, 2022, 11, 895–901.
[0072] The polymerization of δ-thiovalerolactone was repeated according to the conditions in the literature (catalyst: DBU, molar ratio of DBU to δ-thiovalerolactone: 200:1, THF as solvent, monomer concentration: 5 mol / L, polymerization temperature: 20°C, reaction time: 1 hour). The polymerization results were consistent with those in the literature (monomer conversion: 46%, M n =14.3kg / mol, melting point 123°C) similar: M n =14.4kg / mol, monomer conversion rate = 45%, melting point 123°C). Tensile performance test shows ( Figure 2 ), the polymer tensile strength is 4.0MPa, and the elongation at break is 1.9%, which is much lower than the commercial low-density polyethylene (elongation at break 200%, breaking stress 10MPa, literature Nat.Chem.2022,14,294), and has no practical value.
[0073] The present invention tests the mechanical properties of the polyδ-thiovalerolactone obtained in Example 7: mechanical tensile test (such as Figure 4 The experiment shows that the polyδ-thiovalerolactone with a number average molecular weight of 31.4 kg / mol has an elongation at break of 480% and a stress at break of 18.7 MPa; this indicates that the polyδ-thiovalerolactone provided by the present invention is a strong and tough polymer material, and all indicators of the mechanical tensile test are better than those of low-density polyethylene (elongation at break 200%, stress at break 10 MPa, document Nat. Chem. 2022, 14, 294), and is significantly better than the mechanical properties of the δ-thiovalerolactone with the highest molecular weight currently reported.
[0074] Polymer chemistry points out that the molecular weight of a polymer will only show good mechanical properties after it reaches the critical entanglement molecular weight. The entanglement molecular weight can be calculated by the Likhtman-Mcleish theory in polymer physics. For this reason, we determined the entanglement molecular weight of the polymer through oscillatory shear rheology experiments. We measured the dynamic storage modulus (G'), loss modulus (G") and complex viscosity (η) of polyδ-thiovalerolactone at different temperatures. * ) and the rheometer frequency were measured, and the Williams-Randall-Ferry theory was used, and the data analysis software TRIOS (TA Instruments, USA) was used to automatically fit the time-temperature-amplitude superposition at 127°C to obtain Figure 4 . Using the model published by McIlroy (https: / / www.stevenabbott.co.uk / practical-rheology / L-M_Mc.php), the data can be imported to deduce that the entanglement molecular weight of polyδ-thiovalerolactone is 16kg / mol. That is to say, when the molecular weight of the polymer reaches above 16kg / mol, the polymer shows obvious chain entanglement, thereby obtaining polyδ-thiovalerolactone with practical mechanical properties.
[0075] Comparative Example 2
[0076] This comparative example is a reported method of polymerizing δ-thiocarbonylvalerolactone using DBU and aromatic thiols, document: ACS Macro Lett. 2024, 13, 1411.
[0077] The polymerization of δ-thiocarbonylvalerolactone was repeated according to the conditions in the literature (catalyst: DBU, molar ratio of DBU to benzyl mercaptan: 1:1, molar ratio of δ-thiocarbonylvalerolactone to DBU: 100:1, N,N-diethylformamide as solvent, monomer concentration: 5 mol / L, polymerization temperature: 80°C, reaction time: 3 h). The polymerization results were consistent with those in the literature (monomer conversion: 95%, M n =3.3 kg / mol) similarly: M n =3.4 kg / mol, monomer conversion rate = 95%).
[0078] Comparative Example 3
[0079] This comparative example is based on comparative example 2, and the molar ratio of δ-thiocarbonylvalerolactone and DBU is further increased to 250:1 (the catalyst is DBU, the molar ratio of DBU and benzyl mercaptan is 1:1, N,N-diethylformamide is used as solvent, the monomer concentration is 5 mol / L, the polymerization temperature is 80°C, and the reaction time is 3 hours), while other conditions remain unchanged, and the molecular weight of the polymer obtained by polymerization is almost unchanged, and is still 3.3 kg / mol, and the monomer conversion rate = 50%.
[0080] Compared with the polymerization conditions of Example 2 of the present invention and Comparative Example 3, except for the different initiators (alkyl mercaptan is used in Example 2, and aryl mercaptan is used in the comparative example), the other conditions are exactly the same. Example 2 obtains a polyδ-thiocarbonyl valerolactone with a molecular weight of 16.5 kg / mol, while the comparative example only obtains a polymer with a molecular weight of 3.3 kg / mol. Therefore, the alkyl mercaptan initiator in the present invention is an important factor in producing high molecular weight polyδ-thiocarbonyl valerolactone.
Claims
1. A poly-δ-thiovalerolactone, characterized in that: The structure of the polyδ-thiovalerolactone is shown in formula (I): Here, n is greater than or equal to 138.
2. The poly-δ-thiovalerolactone according to claim 1, characterized in that The n is 138-10000; The number average molecular weight of the polyδ-thiovalerolactone is greater than or equal to 16.0 kg / mol; The molecular weight distribution of the polyδ-thiovalerolactone is 1.0-3.
0.
3. A method for preparing polyδ-thiovalerolactone, characterized in that: The steps are as follows: in an organic solvent, in the presence of a main catalyst and an alkylthiol initiator, a compound represented by formula (II) is polymerized at 80 to 120° C.; 4. The preparation method according to claim 3, characterized in that: The main catalyst is one or a mixture of two or more of amidine organic bases, guanidine organic bases, N-heterocyclic carbene organic bases and N-heterocyclic olefin organic bases.
5. The preparation method according to claim 3, characterized in that: The organic solvent is one of hydrocarbon solvents and halogenated aromatic hydrocarbon solvents or a mixture of two or more thereof.
6. The preparation method according to claim 3, characterized in that: The alkylthiol initiator is R 11 SH, HSR 12 SH, R 13 (SH)3, R 14 (SH) 4 or a combination of two or more, R 11 , R 12 , R 13 and R 14 It is a hydrocarbon group of 1 to 20 carbon atoms, and the four are the same or different.
7. The preparation method according to claim 3, characterized in that: The molar ratio of the compound represented by formula (II) to the main catalyst is 100:1-10000:1; the molar ratio of the alkyl mercaptan initiator to the main catalyst is 1:1-100:1; and the polymerization reaction time is 5-1440 minutes.
8. A method for depolymerizing delta-thiovalerolactone according to claim 1, characterized in that: δ-thiovalerolactone is mixed with an acidic catalyst, and distilled at 100-350° C. under normal pressure or reduced pressure to obtain a lactone monomer having a structure shown in formula (VIII):
9. The depolymerization method according to claim 8, characterized in that: The acidic catalyst comprises one or a combination of two or more of zinc chloride, ferrous chloride, ferric chloride, zinc acetate, stannous octoate and phosphomolybdic acid.
10. The depolymerization method according to claim 8, characterized in that: The acidic catalyst accounts for 0.1-50% of the weight of delta-thiovalerolactone.
Citation Information
Patent Citations
Method for reducing oligothioester in 3-mercaptopropionic acid
CN112479953A
Method for preparing sulfur-containing polymer based on isomerization-driven irreversible ring opening polymerization
CN115960355A
Preparation method of poly delta-thiovalerolactone
CN119798665A
Method for preparing sulphur-containing polymer based on isomerisation-driven irreversible ring-opening polymerisation
WO2023061379A2